Ding-Editionen. Vom archäologischen (Be-)Fund übers Corpus ins Netz - Hofmann, Kerstin P.; Grunwald, Susanne; Lang, Franziska; Peter, Ulrike; Rösler, Katja; Rokohl, Louise; Schreiber, Stefan; Tolle, Karsten; Wigg-Wolf, David (e-Forschungsberichte des DAI, 2019)
Corpora, thing-editions, are a central epistemic instrument of knowledge generation for archaeology. Due to digitisation attention has turned once more to various strategies and the politics of representation, and in the course of the debate on (post-)factualism and cultures of knowledge and data we are striving to render the production of knowledge more visible and comprehensible. Following B. Latour’s concept of circulating reference, editions are products of a praxeological connection between the world and representations. This is a report on the ongoing discussion of central questions and objectives for digital corpora and research data management following the FAIR (findable, accessible, inter-operable, re-usable) principle.